Threat cues and attentional bias in blood-injection-injury phobia and snake phobia - Sánchez-Navarro, Juan Pedro; Martínez-Selva, José M.; Kosonogov, Vladimir; Carrillo-Verdejo, Eduvigis; Pineda, Sara; Torrente, Ginesa (Anales de Psicología / Annals of Psychology, 2021)
The aim of this research was to study the effect of a cue signalling the upcoming of a phobic picture on the electrocortical activity provoked by the disorder-relevant stimulus in in blood-injection-injury (BII) phobia and snake phobia. A sample of 13 BII phobia participants, 12 snake phobia individuals and 14 non-phobic controls underwent an S1-S2 task, where S1 was a word that described the content of a subsequent picture (blood-related, snake and neutral) that appeared 2 seconds later (S2). We obtained the P200 and P300 ERP amplitudes provoked by the pictures. Our results reveal that P200 did not differentiate between picture contents in BII phobia while, in contrast, snake and blood-related pictures provoked the largest responses in snake phobia participants. Both blood-related and snake pictures provoked greater P300 amplitudes than neutral pictures in all the groups. Threat cues reduced the electrocortical reaction of the BII, possibly by the elicitation of anticipatory or regulatory responses. These results are indicative of a low automatic, exogenous attention towards the feared stimuli in BII phobia, as revealed by P200, probably related to a lack of attentional bias to the phobic object.